2010
DOI: 10.1186/1471-2164-11-584
|View full text |Cite
|
Sign up to set email alerts
|

An inventory of the Aspergillus niger secretome by combining in silico predictions with shotgun proteomics data

Abstract: BackgroundThe ecological niche occupied by a fungal species, its pathogenicity and its usefulness as a microbial cell factory to a large degree depends on its secretome. Protein secretion usually requires the presence of a N-terminal signal peptide (SP) and by scanning for this feature using available highly accurate SP-prediction tools, the fraction of potentially secreted proteins can be directly predicted. However, prediction of a SP does not guarantee that the protein is actually secreted and current in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 35 publications
5
61
0
2
Order By: Relevance
“…In this study, we observed that 13 out of 22 peptidases with increased abundance after GT exposure were also expressed in A. niger grown under carbon starvation [31,32]. These proteases include An18g01320, An01g01750, PepF (An07g08030), An01g00370, An03g01010, An06g00190, PepA (An14g04710), An02g04690, An08g04640, An09g02830, An12g05960, An03g01660, PepC (An07g03880).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study, we observed that 13 out of 22 peptidases with increased abundance after GT exposure were also expressed in A. niger grown under carbon starvation [31,32]. These proteases include An18g01320, An01g01750, PepF (An07g08030), An01g00370, An03g01010, An06g00190, PepA (An14g04710), An02g04690, An08g04640, An09g02830, An12g05960, An03g01660, PepC (An07g03880).…”
Section: Discussionmentioning
confidence: 71%
“…The proteases with the highest levels of abundance after GT exposure were classified as members of the A1 pepsin family proteases and S53 sedolisin family proteases, based on MEROPS database (merops.sanger.ac.uk) ( Table 4). Interestingly, these two families have been observed to be the most abundant under carbon starvation conditions, in A. niger [31,32].…”
Section: Hydrolytic Enzyme Abundance Is Increased In Response To Gtmentioning
confidence: 99%
“…Gene annotations were manually curated using literature reports, BLAST searches (Altschul et al, 1990) and orthologue clusters from the Aspergillus Genome Database (Arnaud et al, 2010). The presence of secretion signal peptides was predicted following Braaksma et al (2010). The prediction of glycosylphosphatidylinositol (GPI)-anchor sequences was assessed by analysing amino acid sequences obtained from the Aspergillus Genome Database using the fungal BIG-PI prediction server (Eisenhaber et al, 2004) as well as by manual inspection for the C-terminal consensus sequence (de Groot et al, 2003) when automated prediction and literature on (orthologues of) the protein were not in line.…”
Section: Methodsmentioning
confidence: 99%
“…Investigation into the proteomes of A. niger has focused on the exo-proteomes, or the collection of extracellular proteins, under different growth conditions (Adav et al 2010 ;Braaksma et al 2010 ;Lu et al 2010 ;Tsang et al 2009 ). The microsomal proteome following xylose induction has also been examined by shot-gun proteomics (Ferreira de Oliveira et al 2010 ).…”
Section: Transcriptomes and Proteomesmentioning
confidence: 99%